Butterfly vertebra - D. Adam; D. Iftimie; Gina Burduşa; Cristiana Moisescu (Romanian Neurosurgery, 2017)
Background and importance: Butterfly vertebra is an uncommon congenital spinal anomaly, which can be easily mistaken for vertebral fracture, infection or tumor. Clinical presentation: We report the case of a 20-year-old male patient with a 3-year history of intermittent mid-thoracic spinal pain. Local examination showed a mild thoracic kyphoscoliosis. Neurological examination was normal. Computer tomography revealed the presence of a T6 butterfly vertebra associated with morphological anomalies in adjacent vertebral bodies and T6-T9 Schmorl's nodes. MRI scan confirmed the diagnosis and additionally showed a mild spinal stenosis caused by apparent posterior epidural fat hypertrophy. The patient was treated with painkillers and physical therapy. Conclusion: Butterfly vertebra is a benign condition. Once diagnosed, additional diagnostic procedures are not necessary. Neurosurgeons must be aware of this congenital anomaly that should not be confused with a vertebral fracture.